The Influence Of Using Series Pictures Towards Students’ Reading Comprehension In Narrative Text At SMP Negeri 1 Pagaran Simamora Nabolak Academic Years 2021-2022 - Lasnita Lumbantoruan; Dahlia Sirait (Cybernetics: Journal Educational Research and Social Studies, 2022)
The research aims to determine the influence of using series pictures towards students’ reading comprehension in narrative text at Smp Negeri 1 Pagaran .This is research design is experimental research.It was carry out into two groups; The experimental group (VIII 1) was taugh using the series pictures while the control group (VIII 2) was taught without series pictures .The instrument of this research is a multiple choice consisting of 20 question,the test consist of two types ,namely pre-test and post-test to collect data .After collecting data ,the writer then analyzed the test result using –test formula.Based on the data obtained ,it shows that the average pre-test score of the experimental group is 39.33and the control group is 36.33. Meanwhile,the post-test avverage score of the experimental group was 46 and the control group was and the control group was 53,66.Furthmore,it is obtained that the t-test is 1.96 and the table is 1.70 for 0.05 Because the t-test is higher than t-table (1.96>1.70) Ho is rejected and Ha is accepted there is a difference in the post-test mean score between the experimental group and the control group .Based on the result ,it was concluded that using the series pictures was influence in students’ reading comprehension skill in narrative text at SMP N.1 Pagaran.